A Comparative Study About the Purpose of Counseling to Improve the Progress Rate of Low Achiever Students: Exploring the Impact of Counseling in Improving Academic Progress of Low Achiever Students (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This paper presents the role of counseling in progress rate ofstudent. In this paper we provided student performance information as a context andthen briefly elaborate on what appear to be endemic problems. We then elaborateon the role and function of school counselors, counseling philosophy, counseling content, counselingtechniques. Main approaches in counseling and how they can assist in the delivery ofappropriate services to minority schoolchildren and their families. Counseling is arelationship between the counselor and the counselee wherein the latter ishelped to gain better insight into his/her problems, abilities andpotentialities. The counselor creates conducive atmosphere where in thecounselees talk about their problems openly. The counselor listensempathetically and helps them think independently and creatively.